2017
DOI: 10.1093/aje/kww213
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Concentrations of Perfluoroalkyl Substances and Fetal Markers of Metabolic Function and Birth Weight

Abstract: Perfluoroalkyl substances (PFAS) are ubiquitous, persistent chemicals that have been widely used in the production of common household and consumer goods for their nonflammable, lipophobic, and hydrophobic properties. Inverse associations between maternal or umbilical cord blood concentrations of perfluorooctanoic acid and perfluorooctanesulfonate and birth weight have been identified. This literature has primarily examined each PFAS individually without consideration of the potential influence of correlated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
29
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 37 publications
(59 reference statements)
10
29
1
Order By: Relevance
“…Outside of the ALSPAC cohort, our weakly inverse or null results are consistent with those reported in other epidemiologic studies of PFAS and birth size. The PFAS concentrations in this study are generally similar to levels reported in previous studies (Apelberg et al, 2007b;Ashley-Martin et al, 2017;Chen et al, 2012;Fei et al, 2007;Hamm et al, 2010;Manzano-Salgado et al, 2017;Meng et al, 2018;Minatoya et al, 2017;Sagiv et al, 2018;Shoaff et al, 2018;Starling et al, 2017;Whitworth et al, 2012;Woods et al, 2017), though PFNA is lowest in the present study. Studies from Japan (n = 168) (Minatoya et al, 2017), the United States (Maryland) (n = 299) (Apelberg et al, 2007b), Denmark (n = 1,400) (Fei et al, 2007), and Taiwan (n = 429) (Chen et al, 2012) have found evidence of inverse associations of PFOA and PFOS with birth size.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Outside of the ALSPAC cohort, our weakly inverse or null results are consistent with those reported in other epidemiologic studies of PFAS and birth size. The PFAS concentrations in this study are generally similar to levels reported in previous studies (Apelberg et al, 2007b;Ashley-Martin et al, 2017;Chen et al, 2012;Fei et al, 2007;Hamm et al, 2010;Manzano-Salgado et al, 2017;Meng et al, 2018;Minatoya et al, 2017;Sagiv et al, 2018;Shoaff et al, 2018;Starling et al, 2017;Whitworth et al, 2012;Woods et al, 2017), though PFNA is lowest in the present study. Studies from Japan (n = 168) (Minatoya et al, 2017), the United States (Maryland) (n = 299) (Apelberg et al, 2007b), Denmark (n = 1,400) (Fei et al, 2007), and Taiwan (n = 429) (Chen et al, 2012) have found evidence of inverse associations of PFOA and PFOS with birth size.…”
Section: Discussionsupporting
confidence: 92%
“…A third American study (Ohio) (n = 272) analyzed PFAS as a class using Bayesian Hierarchical Linear Models and found that for a 10-fold increase in chemical concentration, the mean difference in birth weight was −11 g for PFAS (Woods et al, 2017). Finally, as we observed in our study for PFOA, PFHxS, and PFNA, other studies have found some evidence of modestly inverse or null associations between PFAS and birth weight (Ashley-Martin et al, 2017;Hamm et al, 2010;Manzano-Salgado et al, 2017;Shoaff et al, 2018;Whitworth et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…However, findings from animal data may not be applicable to humans. To our knowledge, there has been only a few prospective cohort studies that examined associations between early life exposure to PFASs and metabolic function such as adipokine levels (Halldorsson et al 2012;Fleisch et al 2016;Ashley-Martin et al 2017). One study found no evidence of an adverse effect of PFASs exposure on metabolic function in mid-childhood (Fleisch et al 2016) and contrary, the other study suggested that prenatal PFOA exposure significantly associated with leptin and adiponectin levels in female at age of 20 years (Halldorsson et al 2012).…”
Section: Minatoyamentioning
confidence: 99%